Production process of purple pigment with high color fidelity and dyeing uniformity
By precisely controlling the reaction parameters and processing technology in the production process of purple pigment, a stable dye-metal ion precursor is formed, which solves the problems of color fading and unevenness, and achieves high color fidelity and dyeing uniformity, making it suitable for high-end textile and coating fields.
Patent Information
- Application Number
- CN202511601701.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-04
- Publication Date
- 2026-01-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing purple pigments have defects in color durability and dyeing uniformity. The color is prone to fading and unevenness, which limits their application in high-end fields.
By precisely controlling parameters such as the order of raw material addition, reaction temperature, stirring time, and pH value, combined with emulsification dispersion treatment and coating technology, a stable dye-metal ion precursor is formed. The precipitation reaction rate and particle size are controlled, and composite emulsifiers and antioxidant color-preserving agents are used to ensure the stability and uniformity of the colorant's molecular structure.
It achieves long-lasting color fidelity and dyeing uniformity, and improves the colorant's resistance to light, abrasion and washing, making it suitable for high-end textile and coating fields.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of dye processing, more particularly, it relates to a purple colorant production process with high color fidelity and dyeing uniformity. BACKGROUND
[0002] The production process of colorants has been relatively mature, covering a wide range of systems from basic inorganic pigments to high-performance organic dyes. The development of colorants has brought rich color choices to many industries, promoting the progress of industries such as textiles, printing, and coatings, and meeting the diversified needs of color in different fields. In the field of purple colorants, its unique color charm also makes it have important application value in some special high-end fields.
[0003] Currently, in order to prepare purple colorants, the traditional production process usually directly mixes, precipitates and other operations of dyes. When mixing, it may only stir multiple dyes together at will without considering the interaction between the components. The precipitation process is also relatively extensive, without fine control of reaction conditions. In the dispersion and post-processing link, there is a lack of effective means to ensure the uniform distribution of colorant particles, and only conventional dispersion treatment is performed, which is difficult to ensure the quality of the colorant.
[0004] However, the purple colorants on the market currently have obvious defects in use. On the one hand, the color durability is poor, the fidelity is low, the color of the dyed product will fade over time, the initial color is not bright enough, and under the action of light, oxygen or environmental chemicals, the dye molecular structure is easy to degrade, resulting in dull color, gray or even color phase shift. On the other hand, the dyeing uniformity is poor, due to the deficiencies of traditional production process in the precipitation, dispersion and post-processing link, the colorant product has problems such as wide particle size distribution and easy agglomeration, and uneven distribution such as color spots, color stains and stripes may occur during dyeing, which greatly limits the reliable application of purple colorants in high-end fields. SUMMARY
[0005] The purpose of the present application is to overcome the above technical problems, and a purple colorant production process with high color fidelity and dyeing uniformity is provided.
[0006] A purple colorant production process with high color fidelity and dyeing uniformity, comprising the following steps: 1) adding copper sulfate solution to a solution containing Alkali Violet 5BN and Alkali Magenta, stirring uniformly, heating to 78-85℃, to obtain A material; 2) adding sodium ferrocyanide solution to A material for 70-90 min, maintaining the temperature, stirring uniformly, to obtain B material; 3) adding sodium sulfite solution to B material, continuing to stir uniformly, adding sodium ferrocyanide solution to the dissolution device again, stirring uniformly, to obtain C material; 4) Add ammonia water to material C, adjust the pH to 7.5-8, stir for 25-35 minutes to obtain material D; 5) Maintain the temperature of material D and perform emulsification and dispersion treatment to obtain material E; 6) Cool material E to below 60℃ to obtain material F, then filter it by pressure. The resulting filter cake is then dried and pulverized to obtain a pinkish-purple pigment.
[0007] By adopting the above technical solution, step 1) allows copper ions to initially coordinate with Basic Violet 5BN and Basic Fuchsin to form a dye-metal ion precursor, integrating chromophores and creating conditions for forming a composite pigment with a single stable hue. Heating promotes the full dissolution of the dye and intermolecular interactions, improving color fidelity. Step 2) Slowly adding sodium thiosulfate solution controls the precipitation reaction rate, making the pigment particles more uniform in size and more regular in shape, improving dyeing uniformity. Step 3) Sodium sulfite eliminates oxidizing impurities, ensuring long-lasting color fidelity, and sodium thiosulfate is added a second time. Sodium salt ensures complete precipitation of copper ions, enhancing pigment strength and color fastness; Step 4) Adjusting the pH to weakly alkaline stabilizes the pigment crystal form, fine-tuning the surface of pigment particles, reducing the tendency of hard agglomeration, preparing for emulsification and dispersion, and improving dyeing uniformity; Step 5) Dispersing any possible soft agglomerates, making the pigment particles highly monodisperse, reducing the risk of flocculation, and ensuring dyeing uniformity; Step 6) Controlling the cooling to prevent damage to the structure of heat-sensitive dyes, ensuring color fidelity, and subsequent processing to obtain powder products with an ideal particle size range, locking in high color fidelity and dyeing uniformity of the product.
[0008] In summary, the purple pigment production process described in this application has significant advantages in terms of high color fidelity and dyeing uniformity. Regarding color fidelity, precise control of parameters such as the order of raw material addition, reaction temperature, stirring time, and pH value ensures a stable and pure molecular structure for the pigment. The rational utilization of copper and ferrous ions, along with the reducing and protective effect of sodium sulfite, effectively prevents discoloration and fading, guaranteeing color stability during long-term storage and use. Regarding dyeing uniformity, each step emphasizes uniform reaction, such as the slow addition of sodium ferrous sulfate solution and thorough stirring, resulting in a uniform molecular structure for the pigment. Emulsification and dispersion further improves the uniform distribution of pigment particles, ultimately resulting in a pinkish-purple pigment that adheres evenly to the dyed object, achieving uniform dyeing. This process comprehensively considers the stability of the chemical reaction and the uniformity of the physical treatment, which is key to achieving high color fidelity and dyeing uniformity.
[0009] Preferably, the amount of sodium erythritol solution added in step 2) is greater than the amount added in step 3).
[0010] By adopting the above technical solution, in the production process of purple pigment with high color fidelity and dyeing uniformity, the amount of sodium erythorbate solution added in step 2 is greater than that in step 3. Combined with the overall process of this application, it can better achieve slow precipitation and crystal nucleus control, making the generated pigment particles more uniform in size distribution and more regular in shape, further improving dyeing uniformity; at the same time, it ensures that the precipitation reaction can proceed as expected, which helps to maintain the stability and purity of the pigment molecular structure and improve color fidelity.
[0011] Preferably, in step 2), the amount of sodium ferrous sulfate solution added is 90% of the total weight of the sodium ferrous sulfate solution; in step 3), the amount of sodium ferrous sulfate solution added is 10% of the total weight of the sodium ferrous sulfate solution.
[0012] By employing the above technical solution, copper sulfate solution is added to a solution containing basic violet 5BN and basic fuchsin, and heated and stirred to obtain material A. This allows copper ions to initially coordinate with the two dyes to form precursors, laying the foundation for the precipitation reaction. Material B is obtained by slowly adding 90% sodium ferrocyanide solution to material A over 70-90 minutes, which controls the precipitation reaction rate and results in a more uniform particle size distribution of the generated pigment particles. Material C is obtained by adding sodium sulfite solution to material B, followed by the addition of 10% sodium ferrocyanide solution. Sodium sulfite can eliminate oxygen... Chemical impurities ensure color fidelity; the secondary addition of sodium erythorbate increases yield and strengthens pigment structure; adding ammonia to adjust pH to 7.5-8 and stirring yields material D, which helps stabilize the pigment crystal form and modify the particle surface; emulsifying and dispersing material D yields material E, which makes the pigment particles highly monodisperse; cooling, pressing, drying, and pulverizing material E yields a pinkish-purple pigment, which ensures color fidelity and gives the pigment good fluidity and dispersibility, ultimately improving the color fidelity and dyeing uniformity of the purple pigment.
[0013] Preferably, the specific steps of the emulsification and dispersion treatment are as follows: add an emulsion composed of emulsifier OP-10 and emulsifier OS-15 to material D, and treat for a total time of 25-35 minutes to obtain material E.
[0014] By adopting the above technical solution, the composite emulsifier provides "chemical steric stabilization" and the emulsification equipment provides "physical particle size homogenization". The two work together within 25-35 minutes to form the cornerstone of the excellent dispersibility and stability of the pigment. This ensures that the pigment can maintain good redispersibility when it is subsequently filtered, dried and pulverized into powder, which directly determines the dyeing uniformity of the final powder product at the customer's site.
[0015] Preferably, the specific steps of the emulsification and dispersion treatment are as follows: add an emulsion composed of emulsifier OP-10 and emulsifier OS-15 to material D for emulsification, then add EMPO oxidized nanofibers and / or polyethylene glycol-polydimethylsiloxane-polyethylene glycol and mix them evenly. The total treatment time is 25-35 minutes to obtain material E.
[0016] By employing the above technical solution, copper sulfate solution is added to a solution containing basic violet 5BN and basic fuchsin and heated and stirred to obtain material A. Copper ions initially coordinate with dye molecules, laying the foundation for the precipitation reaction and promoting the integration of dye chromophores. Sodium prussiateum solution is added to material A over 70-90 minutes to obtain material B, controlling the precipitation reaction rate and ensuring uniform pigment particle size and regular morphology. Sodium sulfite solution is added, followed by a second addition of sodium prussiateum solution, to obtain material C, eliminating oxidizing impurities, ensuring color fidelity, and making the precipitate skeleton more dense and complete. Ammonia is added to adjust the pH to obtain material D, stabilizing the pigment crystal form, modifying the particle surface, and reducing agglomeration. In material D… An emulsion composed of emulsifiers OP-10 and OS-15 is added for emulsification. Then, EMPO oxidized nanofibers and / or polyethylene glycol-polydimethylsiloxane-polyethylene glycol are added and mixed evenly for 25-35 minutes to obtain material E. EMPO oxidized nanofibers construct a three-dimensional network to prevent particle re-agglomeration and improve dyeing uniformity and pigment strength. Polyethylene glycol-polydimethylsiloxane-polyethylene glycol reduces surface tension and improves color saturation and uniformity. The two work synergistically to construct a stable dispersion system. Material E is then cooled, filtered, dried, and pulverized to obtain a pinkish-purple pigment, ensuring color fidelity and giving the pigment good fluidity and easy dispersibility.
[0017] Preferably, the weight ratio of the EMPO oxidized nanofibers to polyethylene glycol-polydimethylsiloxane-polyethylene glycol is 1:(1-3).
[0018] By employing the above technical solution, copper sulfate solution is added to a solution containing basic violet 5BN and basic fuchsin and heated and stirred to obtain material A. Copper ions initially coordinate with the two dye molecules, laying the foundation for the precipitation reaction and promoting chromophore integration. Sodium ferrous sulfate solution is added to material A over 70-90 minutes to obtain material B. The addition is slow to control the precipitation reaction rate, ensuring uniform particle size distribution of the pigment particles. Sodium sulfite solution is added, followed by a second addition of sodium ferrous sulfate solution to obtain material C. Sodium sulfite prevents dye oxidation and fading, while the second addition of sodium ferrous sulfate ensures complete copper ion precipitation and strengthens the precipitation framework. Ammonia water is added to adjust the pH to 7.5-8 to obtain material D, stabilizing the pigment crystal form and modifying the particle surface. An emulsion composed of emulsifiers OP-10 and OS-15 is added to material D for emulsification. Then, EMPO oxidized nanofibers and polyethylene glycol-polydimethylsiloxane- Polyethylene glycol (PEG) is mixed and treated for 25-35 minutes to obtain material E. A composite emulsifier provides chemical steric stabilization, and physical methods optimize the pigment performance. The weight ratio of EMPO oxidized nanofibers and PEG-polydimethylsiloxane-PEG is controlled at 1:(1-3) to achieve optimal synergy. EMPO oxidized nanofibers construct a three-dimensional spatial steric network to prevent particle re-agglomeration and sedimentation stratification, improve dyeing uniformity, and enhance pigment strength. PEG-polydimethylsiloxane-PEG reduces surface tension, achieving ultimate wetting and penetration, and providing excellent leveling properties. The combination of the two constructs a multi-layered stable dispersion system, broadening the application range of the pigment and ensuring cross-material dyeing consistency. Material E is cooled, filtered, dried, and pulverized to obtain a pinkish-purple pigment. Cooling is controlled to prevent dye structure damage, and subsequent processing ensures that the pigment has good flowability and easy dispersibility.
[0019] Preferably, step 6) further includes a coating process, the specific process of which is as follows: an antioxidant and color-preserving agent is added dropwise to material F. After the addition is completed, the mixture is stirred at a constant temperature for 10-30 minutes to obtain material H, which will then be filtered by pressure. The antioxidant and color-preserving agent is a dispersion containing multi-branched polyether modified epoxy silicone oil and / or tetramethyldivinylsiloxane-bridged biphenylcyclobutene.
[0020] By adopting the above technical solutions, multi-branched polyether modified epoxy silicone oil can perfectly wet and firmly anchor to the surface of pigment particles, forming a chemical coating layer and a hydrophobic protective film, inhibiting pigment fading and discoloration; tetramethyldivinylsiloxane-bridged biphenylcyclobutene can crosslink in situ on the surface of pigment particles to form a stable three-dimensional network polymer film, ensuring color fidelity; the combination of the two can form a composite protective coating with flexibility, density and high strength; controlling the dripping speed and constant temperature stirring can ensure uniform and complete coating reaction, preventing damage to the pigment structure; the treated pigment has strong antioxidant and color retention capabilities, better dispersibility and application leveling properties, and helps improve dyeing uniformity.
[0021] When multi-branched polyether-modified epoxy silicone oil and / or tetramethyldivinylsiloxane-bridged bibenzocyclobutene are compounded at a weight ratio of 3:1, the resulting dispersion, when used in coating treatment, exhibits a synergistic effect, further improving color fidelity and dyeing uniformity. It also enhances stability in high-end dyeing systems, particularly for applications such as anti-counterfeiting coatings and inks.
[0022] Preferably, the solution is obtained by the following method: water is placed in a dissolving device, the temperature is raised to 48-53°C, glacial acetic acid is added and mixed evenly with water, the temperature is raised to 87-93°C, containing basic violet 5BN and basic fuchsin, the temperature is raised to 95-100°C, and the mixture is stirred until completely dissolved to obtain a solution containing basic violet 5BN and basic fuchsin.
[0023] By adopting the above technical solution, the weakly acidic environment can reduce the interfacial tension between the dye and water, accelerate the penetration rate of water molecules into the dye particles, and, combined with the subsequent high temperature of 95-100℃, further shorten the time for complete dye dissolution and avoid the residue of undissolved particles.
[0024] Preferably, the copper sulfate solution in step 1) has a mass concentration of 300-350 kg / 3000 L and a temperature of 75-85 °C.
[0025] By adopting the above technical solution, adding copper sulfate solution of specific mass concentration and temperature to a solution containing basic violet 5BN and basic fuchsin enables copper ions to better coordinate with the two dye molecules under heating conditions, forming a dye-metal ion precursor, laying the foundation for subsequent precipitation reaction, helping to integrate the chromophores of the two dyes, obtaining a composite pigment with a single, stable hue, and improving color fidelity; at the same time, it promotes the full dissolution of dyes and intermolecular interactions.
[0026] Preferably, the sodium ferrous sulfate solution is obtained by heating water to 78-88°C, adding soda ash, dissolving it completely, adding sodium ferrous sulfate, and maintaining the pH value at 9-9.5 to obtain the sodium ferrous sulfate solution.
[0027] By adopting the above technical solutions, an alkaline and stable environment is created to prevent the decomposition of sodium erythritol, prevent the introduction of impurities that interfere with the reaction, ensure the accuracy of the reaction, and guarantee color fidelity from the source. Preheating and alkalinity work together to promote the rapid and complete dissolution of sodium erythritol, improve the efficiency of subsequent reactions, and facilitate the generation of finer particles with a more concentrated particle size distribution, thereby improving dyeing uniformity. Precise pH control optimizes the overall process stability, ensures the consistency of the properties of the raw material solution between batches, and ensures the stability and reproducibility of the final colorant product quality.
[0028] In summary, this application includes at least one of the following beneficial technical effects: 1. Copper sulfate complexes with Basic Violet 5BN and Basic Fuchsin at a specific temperature to form a dye-metal ion precursor, creating conditions for the formation of composite pigments with a single, stable hue and improving color fidelity. 2. Slowly add sodium ferrous sulfate solution to control the precipitation reaction rate, making the pigment particle size distribution more uniform, reducing color spots and streaks, and improving dyeing uniformity; 3. The reducing effect of sodium sulfite prevents the dye from oxidizing and fading. The secondary addition of sodium pyrite makes the pigment particles more compact, ensuring color fidelity and color fastness. Detailed Implementation
[0029] The present application will be further described in detail below with reference to the embodiments.
[0030] Partial ingredient descriptions: Emulsifier OP-10, alkylphenol polyoxyethylene ether, HLB value 14.5; Emulsifier OS-15, fatty alcohol polyoxyethylene ether, HLB value 14.5; Sodium prussiatetramine, CAS No. 13601-19-9; The EMPO oxidized nanofiber brand and model is Tianlu Nano TL010-2, 2,2,6,6-tetramethylpiperidine oxide; The molecular structure of polyethylene glycol-polydimethylsiloxane-polyethylene glycol is as follows, where n and m are both 10-30;
[0031] Multi-branched polyether modified epoxy silicone oil, IOTA ESM32; Tetramethyldivinylsiloxane-bridged benzocyclobutene CSA No. 117732-87-3. Example
[0032] Example 1 A production process for a purple pigment with high color fidelity and uniform dyeing includes the following steps: The solution was obtained by the following method: Place 0.24 tons of water in a dissolving apparatus and heat to 50°C. Then add 0.12 kg of glacial acetic acid and mix thoroughly with the water. Heat to 80°C, add 1.50 kg of Basic Violet 5BN and 0.64 kg of Basic Fuchsin, and heat to 95°C. Stir at a rate of 500 r / min until completely dissolved (observe the spots with filter paper to check for any undissolved particles). A solution containing Basic Violet 5BN and Basic Fuchsin is obtained.
[0033] Copper sulfate solution is obtained by the following method: Heat 30.00L of water to 80℃, then add 3.24kg of copper sulfate and let it dissolve completely to form a clear blue copper sulfate solution.
[0034] Sodium prussiatetracycline solution is obtained by the following method: Heat 30.00L of water to 80℃, then add 1.86kg of soda ash. After it is completely dissolved, add 2.36kg of sodium ferrous sulfate to maintain the pH value at 9.5, thus obtaining a sodium ferrous sulfate solution.
[0035] Sodium sulfite solution is obtained by the following method: Heat 1.00L of water to 60℃, add 0.074kg of sodium sulfite, and dissolve to form a sodium sulfite solution.
[0036] 1) Add all the copper sulfate solution to the dissolving apparatus (dissolving tank) containing the solution of basic purple 5BN and basic fuchsin, stir for 4 minutes to make it fully mixed, the stirring speed is 500 r / min, and heat to 80℃ to obtain material A; 2) Add all of the 90wt% sodium ferrous sulfate solution to material A over 80 minutes, maintain the temperature at 80℃, and continue stirring until it is fully mixed to obtain material B; 3) Add all the sodium sulfite solution to material B and continue stirring until homogeneous. Then add the remaining 10wt% sodium ferrous sulfate solution to the dissolving device and stir it thoroughly with the sodium sulfite solution and material B to obtain material C. 4) Add 0.80 kg of ammonia water (mass fraction of 20%) to material C, adjust the pH to 8, stir for 30 min, and obtain material D; 5) Maintain the temperature of material D at 80℃, then add the emulsion composed of 0.172kg emulsifier OP-10 and 0.08kg emulsifier OS-15 to material D, and continue stirring. The emulsification treatment time is 30 minutes to obtain material E.
[0037] 6) Cool material E to below 60℃, such as 55℃, to obtain material F; then transfer it to a filter press for filtration. The resulting filter cake (containing 20% solids) is then dried in an oven and pulverized in a pulverizer. After sieving through a 100-mesh sieve, a pinkish-purple pigment is obtained.
[0038] Example 2 The difference between Example 2 and Example 1 is that: In step 1), the heating temperature is 85℃; In step 2), a 90wt% sodium ferrous sulfate solution is added to material A over 70 minutes; In step 4), the pH is 7.5, and the mixture is stirred for 35 minutes.
[0039] Example 3 The difference between Example 3 and Example 1 is that: In step 1), the heating temperature is 78℃; In step 2), a 90wt% sodium ferrous sulfate solution is added to material A over 90 minutes. In step 4), the pH is 8, and the mixture is stirred for 25 minutes.
[0040] Example 4 The difference between Example 4 and Example 1 lies in the specific steps of the emulsification and dispersion treatment: Then, add the emulsion composed of 0.172 kg of emulsifier OP-10 and 0.08 kg of emulsifier OS-15 to material D, and continue stirring. The emulsification treatment time is 20 min. Then, add 0.05 kg of EMPO oxidized nanofiber and 0.05 kg of polyethylene glycol-polydimethylsiloxane-polyethylene glycol and mix them evenly. The treatment time is 10 min to obtain material E.
[0041] Example 5 The difference between Example 5 and Example 4 is that 0.05 kg of polyethylene glycol-polydimethylsiloxane-polyethylene glycol was replaced with an equal amount of EMPO oxidized nanofibers.
[0042] Example 6 The difference between Example 6 and Example 4 is that 0.05 kg of EMPO oxidized nanofibers were replaced with an equal amount of polyethylene glycol-polydimethylsiloxane-polyethylene glycol.
[0043] Example 7 The difference between Example 7 and Example 4 is that step 6) further includes a coating process, the specific process of which is as follows: The antioxidant color-preserving agent is obtained by the following method: 0.10 kg of multi-branched polyether modified epoxy silicone oil and 0.02 kg of tetramethyldivinylsiloxane bridged biphenylcyclobutene are weighed and dissolved in 0.10 kg of isopropanol and 0.02 kg of xylene to obtain the antioxidant color-preserving agent.
[0044] Add all the above antioxidant and color-preserving agents to material F at a rate of 2 kg / min. After the addition is complete, stir at a constant temperature of 55°C for 30 minutes to obtain material H. Then transfer it to a filter press for filtration. The resulting filter cake (containing 20% solids) is dried in an oven and then pulverized in a pulverizer. After sieving through a 100-mesh sieve, a pinkish-purple pigment is obtained.
[0045] Example 8 The difference between Example 8 and Example 7 is that 0.02 kg of tetramethyldivinylsiloxane-bridged bibenzocyclobutene was replaced with multi-branched polyether modified epoxy silicone oil.
[0046] Example 9 The difference between Example 9 and Example 7 is that 0.10 kg of multi-branched polyether modified epoxy silicone oil was replaced with tetramethyldivinylsiloxane-bridged bibenzocyclobutene.
[0047] Comparative Example
[0048] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that there is no emulsification treatment in step 5), and the D material obtained in step 4) is directly used in step 6).
[0049] Application examples Application Example 1
[0050] The application of a purple pigment with high color fidelity and dyeing uniformity is as follows:
[0051] Application in the textile field: Pure cotton poplin (warp and weft density 133×72, weight 120g / m²) was selected as the carrier. The dye liquor was prepared according to the mass ratio of dye (purple dye with high color fidelity and dyeing uniformity obtained in Example 1): water: binder (Yoshida E0503 water-based acrylic emulsion) = 1:10:2. The pad dyeing process was adopted with a pad-dyeing rate of 70%. The dyeing was pre-dried at 105℃ for 5 min, baked at 130℃ for 5 min, and placed at 25℃ and 60% humidity for 24 h to prepare dyed fabric samples. The sample size was 200mm×200mm. Several textile parallel samples were used in each group for the experiments of this application.
[0052] In the field of coatings: Using EBECRYL8110 polyurethane acrylate resin high-gloss clear varnish as the base material, the colorant (the purple colorant with high color fidelity and dyeing uniformity obtained in Example 1) and clear varnish were mixed at a mass ratio of 1:10. The coating was applied by spraying at a pressure of 0.4 MPa and a distance of 200 mm. It was then UV cured at a wavelength of 365 nm for 1 min, followed by drying at 80°C for 10 min. The coating was then left to stand at 25°C and 60% humidity for 24 h to prepare coating samples. The substrate was tinplate (150 mm × 100 mm, 0.3 mm thick). Several parallel samples of the coating were obtained from each group for the experiments in this application.
[0053] Application Example 2-10 The difference between Application Example 2-10 and Application Example 1 is that the source of the purple pigment with high color fidelity and dyeing uniformity is different, as shown in Table 1. Table 1. Sources of purple pigments with high color fidelity and dyeing uniformity in Application Examples 1-10.
[0054] Experimental Analysis
[0055] Experiment 1: Staining Uniformity Test Samples: textile parallel samples and coating parallel samples ASTM D2244: American Society for Testing and Materials standard for measuring color difference in opaque coatings and coatings.
[0056] CIELab* color space: International Commission on Illumination (CIE) standard, quantifying color difference (ΔE value), where: Grade A: ΔE<1: Color difference imperceptible to the naked eye (requirement for high-end textiles).
[0057] Grade B: 1≤ΔE<2: Slight color difference (requires careful observation).
[0058] Grade C: ΔE≥2.5: Significant color difference (affecting appearance quality) Experiment 3: Color Fidelity Test Test method: The samples were textile parallel samples and coating parallel samples. According to GB / T8427-2019 "Textiles - Test for color fastness - Color fastness to artificial light: Xenon arc", the xenon arc lamp aging test chamber was used. The test conditions were: irradiance 0.84W / (m²・nm) (340nm wavelength), blackboard temperature 65℃, relative humidity 60%, and irradiation time 168h. Color difference measurement: Before and after the test, the color parameters (L*, a*, b*) of the sample are measured using a spectrophotometer. The color difference ΔE*ab(light) between the sample and the standard color sample after the test is calculated. At the same time, the color change grade is evaluated in accordance with GB / T250-2008. Color fastness test for rubbing: The samples were textile parallel samples and coating parallel samples according to GB / T3920-2008. The color fastness tester for rubbing was used. Dry rubbing: The sample was rubbed 10 times with a standard rubbing cloth (cotton) at a pressure of 9 kPa; Wet rubbing: The rubbing cloth had a moisture content of 100% and was rubbed 10 times. Color difference measurement: After rubbing, measure the color difference ΔE*ab (molarity) between the rubbed area of the sample and the standard color sample, and evaluate the color change grade. Color fastness test for washing: The sample is a textile parallel sample. According to GB / T3921-2008, the color fastness tester for washing was used. The test conditions were: soap concentration 5g / L (phosphate-free laundry detergent), temperature (40±2)℃, liquor ratio 1:50, washing time 30min, followed by rinsing with cold water for 5min and drying at 105℃. Color difference measurement: After washing, measure the color difference ΔE*ab(wash) between the sample and the standard color sample, and evaluate the color change grade. Table 2 Experimental data from Application Examples 1-10
[0059] Combining Application Example 1 and Application Example 10 with Table 1, it can be seen that the ΔE value of Application Example 10 is grade C (ΔE≥3.5), and the ΔE value of Application Example 1 is grade C (1≤ΔE<2). Furthermore, the color difference grades of the parallel samples of the coating and textile in Application Example 10 are lower than those of Application Example 1. This indicates that the purple pigment with high color fidelity and dyeing uniformity prepared by Application Example 1 using Example 1 of this application has better color fidelity and dyeing uniformity.
[0060] Comparing Application Examples 1, 5-6, and 4, it can be seen that Application Example 4 achieves a ΔE of Grade A, while Application Examples 1 and 5-6 achieve Grade B. Regarding color fidelity, Application Example 4, after undergoing tests for lightfastness, abrasion resistance, and water resistance, shows color difference grades of 4-5 or higher, even reaching Grade 5. This indicates that Application Example 4, using the EMPO oxidized nanofiber and polyethylene glycol-polydimethylsiloxane-polyethylene glycol compound from Example 4, achieves a synergistic effect. Combined with the emulsification process of this application, the resulting pinkish-purple pigment exhibits high dyeing uniformity and color fidelity when applied to fabric dyeing or coating production. Therefore, it has excellent practicality for high-end applications.
[0061] Comparing Application Examples 4, 8-9, and 7, it can be seen that Application Example 7, in terms of color fidelity, achieved a color difference level of 5 or higher after performance tests such as light resistance, abrasion resistance, and water resistance. Application Examples 4 and 8-9 only achieved a small portion of the 5-level color fidelity. This indicates that the antioxidant color-preserving agent used in Example 7, which incorporates both multi-branched polyether-modified epoxy silicone oil and tetramethyldivinylsiloxane-bridged benzocyclobutene, has a synergistic effect, particularly in light resistance and water resistance. This enhances the dyeing effect of the pinkish-purple pigment when applied to coatings or fabric dyeing, preventing color distortion over time.
[0062] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A production process for a purple pigment with high color fidelity and uniform dyeing, characterized in that, Includes the following steps: 1) Add copper sulfate solution to a solution containing basic violet 5BN and basic fuchsin, stir well, and heat to 78-85℃ to obtain material A; 2) Add sodium ferrous sulfate solution to material A over 70-90 minutes, maintain the temperature, and stir until homogeneous to obtain material B; 3) Add sodium sulfite solution to material B, continue stirring until homogeneous, then add sodium ferrous sulfate solution to the dissolving device again, stir until homogeneous, and obtain material C; 4) Add ammonia water to material C, adjust the pH to 7.5-8, stir for 25-35 minutes to obtain material D; 5) Maintain the temperature of material D and perform emulsification and dispersion treatment to obtain material E; 6) Cool material E to below 60℃ to obtain material F, then filter it by pressure. The resulting filter cake is then dried and pulverized to obtain a pinkish-purple pigment.
2. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that: The amount of sodium chlorophyll solution added in step 2) is greater than the amount added in step 3).
3. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that: In step 2), the amount of sodium ferrous sulfate solution added is 90% of the total weight of the sodium ferrous sulfate solution; in step 3), the amount of sodium ferrous sulfate solution added is 10% of the total weight of the sodium ferrous sulfate solution.
4. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that, The specific steps of the emulsification and dispersion treatment are as follows: add an emulsion composed of emulsifier OP-10 and emulsifier OS-15 to material D, and the total treatment time is 25-35 minutes to obtain material E.
5. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that: The specific steps of the emulsification and dispersion treatment are as follows: add an emulsion composed of emulsifier OP-10 and emulsifier OS-15 to material D for emulsification, then add EMPO oxidized nanofibers and / or polyethylene glycol-polydimethylsiloxane-polyethylene glycol and mix them evenly. The total treatment time is 25-35 minutes to obtain material E.
6. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 5, characterized in that: The weight ratio of the EMPO oxidized nanofibers to polyethylene glycol-polydimethylsiloxane-polyethylene glycol is 1:(1-3).
7. A production process for a purple pigment with high color fidelity and dyeing uniformity according to any one of claims 1-6, characterized in that: Step 6) also includes a coating process, the specific process of which is as follows: Antioxidant and color-preserving agent is added dropwise to material F. After the addition is complete, the mixture is stirred at a constant temperature for 10-30 minutes to obtain material H, which will then be filtered by pressure.
8. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that, The solution was obtained by the following method: Water is placed in a dissolving apparatus and heated to 48-53°C. Glacial acetic acid is then added and mixed thoroughly with the water. The temperature is then raised to 87-93°C. The mixture contains Basic Violet 5BN and Basic Fuchsin. The temperature is then raised to 95-100°C and stirred until completely dissolved to obtain a solution containing Basic Violet 5BN and Basic Fuchsin.
9. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that: The copper sulfate solution in step 1) has a mass concentration of 300-350 kg / 3000 L and a temperature of 75-85 °C.
10. The production process for a purple pigment with high color fidelity and dyeing uniformity according to claim 1, characterized in that, The sodium ferrous sulfate solution was obtained by the following method: Heat water to 78-88℃, then add soda ash. After it is completely dissolved, add sodium ferrous sulfate to maintain the pH value at 9-9.5, thus obtaining a sodium ferrous sulfate solution.